Early pulmonary rehabilitation after acute exacerbation of COPD: a randomised controlled trial - Jakob L. Kjærgaard; Carsten B. Juhl; Peter Lange; Jon T. Wilcke (ERJ Open Research, 2020)
Objectives The aim of this study was to establish whether early pulmonary rehabilitation after severe exacerbation of chronic obstructive pulmonary disease (COPD) reduces mortality and hospital admissions, and increases physical performance and quality of life compared to rehabilitation initiated later in the stable phase of COPD. Methods In a randomised controlled trial of 150 patients hospitalised with an exacerbation of COPD, participants were allocated to pulmonary rehabilitation either within 2 weeks after discharge or the same rehabilitation programme but initiated 2 months after discharge. Results Early pulmonary rehabilitation did not prolong time to first hospital admission or time to death (hazard ratio 0.79, 95% CI 0.47–1.23, p=0.33) compared to rehabilitation in stable phase. However, 2 months after inclusion, pulmonary rehabilitation resulted in a significantly better improvement in the incremental shuttle walk test (33.9 m, 95% CI 4.18–63.7, p=0.02) compared to that in the stable phase. The difference in the endurance shuttle walk test was of borderline significance (140 s, 95% CI −2.03–282.76, p=0.05), but there was no significant difference concerning the COPD assessment test (−1.43 points, 95% CI −3.44–0.59, p=0.17). Conclusion Early pulmonary rehabilitation after acute exacerbation of COPD led to a faster improvement in physical performance compared to rehabilitation initiated later in the stable phase, but did not improve survival or prolong time to hospital readmission.